RANCANG BANGUN SISTEM PEMBELAJARAN JARAK JAUH MENGGUNAKAN E-LEARNINGPADA MASA PANDEMI COVID-19 MENGGUNAKAN DATABASE MYSQL - Indra Maulana; Ika Kartika (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2021)
On March 24, 2020 the Minister of Education and Culture of the Republic of Indonesia issued Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of COVID, in the Circular it was explained that the learning process was carried out at home through online/distance learning to provide a learning experience. meaningful to students. Studying at home can be focused on life skills education, including regarding the Covid-19 pandemic. Online learning students have the flexibility of learning time, can learn anytime and anywhere. Students can interact with teachers using several applications such as classroom, video conference, telephone, live chat, zoom meeting or via whatsapp group. This learning is an educational innovation to answer the challenge of the availability of varied learning resources. The purpose of this research is to find out how the implementation of the learning process carried out during the Covid-19 pandemic at SMK Ulil Albab, implement e-learning learning methods to support the learning process during the pandemic, provide solutions for schools to monitor the learning process during the pandemic with applications. e-learning designed according to school needs. For that, the author is interested in developing to analyze "Design of a Distance Learning System Using E-Learning during the Covid-19 Pandemic Using MYSQL Databases at Ulil Albab Vocational School"